Improved differential cryptanalysis on Generalized Feistel Schemes - Tjuawinata, Ivan (2019)
Nachef et al. used differential cryptanalysis to study four types of Generalized Feistel Scheme (GFS). They gave the lower bound of maximum number of rounds that is indistinguishable from a random permutation. In this paper, we study the security of several types of GFS by exploiting the asymmetric property. We show that better lower bounds can be achieved for the Type-1 GFS, Type-3 GFS and Alternating Feistel Scheme. Furthermore, we give the first general results regarding to the lower bound of the Unbalanced Feistel Scheme.